Vemurafenib and ipilimumab: a promising combination? results of a case series - Hassel, Jessica C.; Strobel, Sophia; Meiss, Frank; Meier, Friedegund; Dimitrakopoulou-Strauss, Antonia; Jäger, Dirk; Enk, Alexander (OncoImmunology, 2016)
The purpose of combining targeted agents and immunotherapy is to achieve a chance of long-term tumor control in highly advanced patients. Between April 2012 and December 2013, 10 patients with metastatic melanoma were treated with a combination treatment of vemurafenib and ipilimumab as an individual treatment decision after detailed information and giving written informed consent. All the patients had advanced symptomatic disease, seven with elevated serum lactate dehydrogenase (LDH) levels and six with brain metastases on MRI. After clinical improvement under vemurafenib monotherapy (median 11.5 weeks), four cycles of ipilimumab were administered additionally. Combination treatment was tolerated well, with only two patients developing ≥ grade 3 elevation of transaminases; this was asymptomatic and resolved on cessation of BRAF inhibitor treatment. Staging 12 weeks after initiation of ipilimumab revealed partial response for five patients, stable disease for two, and disease progression for three. Of the seven patients with disease control, we stopped vemurafenib for five, to determine whether ipilimumab treatment led to disease control. Two revealed progressive disease 2 mo later, and received vemurafenib again, but for three the disease was controlled for at least a year, and two are still in partial remission without any further treatment. Progression-free survival was a median of 8.0 mo (95% CI 4.8-11.2), overall survival (OS) was 13.0 mo (95% CI 5.0-21.0), and four patients are still alive. In conclusion, the combination of vemurafenib and ipilimumab was well tolerated and clinical outcome was promising. The combination of targeted and immunotherapies is currently addressed in clinical trials.